Determinação do fenótipo sexual em uma criança com Mosaicismo 45,X/46,X,Idic(Yp): importância da proporção relativa da linhagem 45,X no tecido gonadal - Guedes, Alexis Dourado [UNIFESP] (2006)
We report here on a girl who, despite her 45,X/46,X,der(Y) karyotype, showed no signs of virilization or physical signs of the Ullrich-Turner syndrome [UTS], except for a reduced growth rate. After prophylactic gonadectomy due to the risk of developing gonadoblastoma, the gonads and peripheral blood samples were analyzed by fluorescence in situ hybridization [FISH] and polymerase chain reaction [PCR] to detect Y-specific sequences. These analyses allowed us to characterize the Yderived chromosome as being an isodicentric Yp chromosome [idic(Yp)] and showed a pronounced difference in the distribution of the 45,X/46,X,idic(Yp) mosaicism between the two analyzed tissues. It was shown that, although in peripheral blood almost all cells (97.5%) belonged to the idic(Yp) line with a duplicated SRY gene, this did not determine any degree of male sexual differentiation in the patient, as in the gonads the predominant cell line was 45,X (60%).